Performance Employee Reviewed From Professionalism, Employee Appreciation, Commitment, and Employee Job Placement - I Kadek Sarraswati Dian Widhyanita; Istiatin; Sudarwati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to test and analyze the influence of professionalism, appreciation, job placement on employee performance at KPP Pratama Surakarta. This type of research uses quantitative descriptive. The population in this study were all employees of KPP Pratama Surakarta, which were 101 people. The research sample was the entire population of 101 people or all employees of KPP Pratama Surakarta. The sampling technique was carried out by means of saturated or census samples.The data analysis technique used is multiple linear regression analysis. The results of the study show thatProfessionalism has a positive and significant influence on employee performance at KPP Pratama Surakarta, Awards have a positive and significant influence on employee performance at KPP Pratama Surakarta, Organizational commitment has a positive and significant influence on employee performance at KPP Pratama Surakarta, and Job placement has a positive and significant influence on employee performance at KPP Pratama Surakarta. Keywords: professionalism, appreciation, organizational commitment, job placement, performance